Serum Aquaporin 4-Immunoglobulin G Titer and Neuromyelitis Optica Spectrum Disorder Activity and Severity: A Systematic Review and Meta-Analysis - Liu, Jia; Tan, Guojun; Li, Bin; Zhang, Jingze; Gao, Ying; Cao, Yuanbo; Jia, Zhen; Sugimoto, Kazuo (Frontiers in Neurology, 2021)
Background: Aquaporin 4-immunoglobulin G (AQP4-IgG) plays a major role in the pathogenesis of neuromyelitis optica spectrum disorder (NMOSD). Seropositive status for this antibody has become one of the required indicators for NMOSD diagnosis. Objective: Our goal was to systematically review and perform a meta-analysis of the current works of literature evaluating the clinical relevance of serum AQP4-IgG titer in patients with NMOSD. We sought to determine whether AQP4-IgG could indicate disease activity or severity, in addition to its diagnostic value in NMOSD. Methods: Electronic databases were searched for published literature, yielding 4,402 hits. Of the 124 full articles screened, 17 were included in the qualitative analysis and 14 in the meta-analysis. Results: There were no significant differences in serum AQP4-IgG titers between the relapse and remission phases in patients with NMOSD (standard mean difference [SMD]: 0.32, 95% CI [−0.10, 0.74], P = 0.14). Subgroup meta-analysis of AQP4-IgG detected by cell-based assays (CBA), an AQP4-IgG testing method recommended by the 2015 international consensus diagnostic criteria for NMOSD, confirmed the aforementioned result (SMD: 0.27, 95% CI [−0.01, 0.55], P = 0.06). Moreover, the serum AQP4-IgG titer was positively correlated with the number of involved spinal cord segments (correlation coefficient [COR]: 0.70, 95% CI [0.28-0.89], P = 0.003) and the Expanded Disability Status Scale score (COR: 0.54, 95% CI [0.06-0.82], P = 0.03) in the attack phase in patients with NMOSD. Conclusions: The present study systematically assessed the association between serum AQP4-IgG titer and NMOSD activity and severity. The results demonstrated that the serum AQP4-IgG titer was not associated with disease activity but indicated the disease severity in the attack phase in patients with NMOSD. A further meta-analysis with a larger number of studies that employed standardized AQP4-IgG assays and detected attack-remission paired samples from the same patients with detailed medication information will be required to confirm our findings and shed more light on optimizing clinical AQP4-IgG monitoring.